Experimental studies of activated carbon/graphite composite adsorbent for improved performance of packed and coated bed adsorption cooling system - Satheeshkumar P; Immanuel Selwynraj A (Results in Engineering, 2024)
In this study, composite adsorbents are developed by using various compositions of activated carbon (AC)/polyvinyl alcohol (PVA) with graphite powder (GP). The optimal adsorption material chosen for the adsorption cooling system (ACS) is found to be composite A, which comprises 93 % AC, 5 % graphite powder, and 2 % PVA. This selection is made based on the physical characterization of the composite materials by BET, FESEM, adsorption capacity, desorption capacity and thermal conductivity tests. The specific cooling power (SCP), coefficient of performance (COP), and exergetic COP of the adsorption chiller are experimentally evaluated. By maintaining the optimal desorption and condenser temperatures (Tdes = 70 °C and Tcon = 35 °C), the maximum COP, SCP and exergetic COP of the system are found to be 0.582, 206 W/kg and 0.19 for packed bed and 0.738, 261.37 W/kg and 0.25 for coated bed, when the adsorption temperature (Tads) = 30 °C and evaporation temperature (Teva) = 25 °C. The Freundlich isotherms exhibit a better correlation with the vapour pressure of methanol. The samples exhibited no deformations after 17 adsorption/desorption cycles, confirming the durability of the activated carbon. The more uniform coating thickness and smooth surface structure could ensure long-term stability and performance of the adsorbent.